Computed Tomography-Based Assessment of Transvalvular Pressure Gradient in Aortic Stenosis - Franke, Benedikt; Brüning, Jan; Yevtushenko, Pavlo; Dreger, Henryk; Brand, Anna; Juri, Benjamin; Unbehaun, Axel; Kempfert, Jörg; Sündermann, Simon; Lembcke, Alexander; Solowjowa, Natalia; Kelle, Sebastian; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: In patients with aortic stenosis, computed tomography (CT) provides important information about cardiovascular anatomy for treatment planning but is limited in determining relevant hemodynamic parameters such as the transvalvular pressure gradient (TPG). Purpose: In the present study we aimed to validate a reduced order model method for assessing TPG in aortic stenosis using computed tomography data. Methods: TPGCT was calculated using a reduced order model requiring the patient-specific peak-systolic aortic flow rate (Q) and the aortic valve area (AVA). AVA was determined by segmentation of the aortic valve leaflets whereas Q was quantified based on volumetric assessment of the left ventricle. For validation, invasively measured TPGcatheter was calculated from pressure measurements in the left ventricle and the ascending aorta. Altogether, 84 data sets of patients with AS were used to compare TPGCT against TPGcatheter. Results: TPGcatheter and TPGCT were 50.6 ± 28.0 mmHg and 48.0 ± 26 mmHg, respectively (p = 0.56). Bland-Altman analysis revealed good agreement between both methods with a mean difference in TPG of 2.6 mmHg and a standard deviation of 19.3 mmHg. Both methods showed good correlation with r = 0.72 (p < 0.001). Conclusions: The presented CT-based method allows assessment of TPG in patients with aortic stenosis, extending the current capabilities of cardiac CT for diagnosis and treatment planning.